Method for producing sustainable aviation fuel by utilizing straws
By using a catalyst preparation method of phosphoric acid, template agent and cerium nitrate as a cerium source in a specific molar ratio in the process of preparing aviation fuel from straw, the catalyst structure and acid sites are optimized, the problem of low ethanol yield is solved, and efficient ethanol production is achieved.
Patent Information
- Application Number
- CN202510778198.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-11
- Publication Date
- 2025-09-12
- Estimated Expiration
- 2045-06-11
AI Technical Summary
In the existing process of preparing aviation fuel from straw, especially in the step of generating ethanol from syngas, the ethanol yield is low, and the efficiency and economic feasibility need to be optimized.
A new catalyst preparation method is adopted. By introducing a specific molar ratio of phosphoric acid and template agent into the primary molecular sieve catalyst and adding cerium nitrate as a cerium source, CeO2 nanoparticles are formed, the catalyst structure and acid sites are optimized, and the diffusion efficiency and hydrogenation rate of synthesis gas are improved.
The ethanol yield was significantly increased to 384.4 g/kgcat/h, improving the efficiency and economy of fuel production.
Smart Images

Figure CN120624076A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aviation fuel, and particularly relates to a method for producing sustainable aviation fuel by utilizing straw. Background Art
[0002] The production of sustainable aviation fuel from straw is primarily achieved through biochemical or thermochemical conversion processes. For example, a four-step process for converting biomass straw into aviation fuel involves converting straw into syngas, syngas into ethanol, ethanol into ethylene, and finally ethylene into aviation fuel.
[0003] The first step involves converting biomass into syngas (syngas) rich in carbon monoxide, carbon dioxide, and hydrogen through gasification; this technology has been extensively researched and has proven applications. The second step involves converting syngas into ethanol, which can be achieved through microbial fermentation or chemical catalysis. The third step involves dehydrating ethanol to produce ethylene, a relatively mature chemical process. The fourth step involves further converting ethylene into various liquid hydrocarbons, including alkanes for aviation fuel, through chemical reactions such as polymerization and hydrogenation. This process is widely used in the petrochemical industry and is a relatively mature technology.
[0004] However, the efficiency, cost, and economic feasibility of the entire process still need to be further optimized. In particular, increasing the ethanol yield in the second step, the synthesis gas to ethanol process, remains a current research focus. Summary of the Invention
[0005] To solve the problems existing in the background technology, the present invention provides a method for producing sustainable aviation fuel using straw, which significantly improves the ethanol yield in the aviation fuel production process.
[0006] In order to achieve the above object, the present invention provides the following technical solutions: A method for producing sustainable aviation fuel using straw comprises first converting the straw into synthesis gas; then subjecting the synthesis gas to a catalytic reaction with dimethyl ether over a primary molecular sieve catalyst; and then subjecting the resulting catalytic product to a catalytic reaction over a secondary metal catalyst, followed by separation to obtain ethanol; then converting the ethanol into ethylene; and finally converting the ethylene into aviation fuel. The preparation method of the primary molecular sieve catalyst is as follows: A1. Mix 100g of phosphoric acid solution with 290-310g of deionized water, add a template, and add 170-180g of aluminum source, 0.16-0.2g of cerium source, and 50-55g of silica sol under stirring to form a uniform gel. A2. Transfer the gel obtained in A1 to a high-pressure reactor, microwave-heat at 160±5°C, and crystallize for 5.5-6.5 hours. Centrifuge and wash the product until neutral, dry it at 100-110°C for 12-13 hours, and calcine it at 550±10°C for 3.8-4.2 hours to remove the template to obtain a calcined product. A3, immerse the calcined product obtained in A2 in a zinc nitrate solution, dry it, and calcine it at 450±10°C for 3-3.5h to obtain a zinc-loaded product; A4. The zinc-loaded product obtained in A3 is dealuminated with a citric acid solution to form mesopores (to improve diffusion efficiency), and then calcined and activated again to obtain a first-stage molecular sieve catalyst.
[0007] Furthermore, in A1, the wt% of the phosphoric acid solution is ≥85%.
[0008] Furthermore, in A1, the template is di-n-butylamine; the aluminum source is aluminum isopropoxide; and the cerium source is cerium nitrate.
[0009] Furthermore, in A1, the SiO2 content in the silica sol is 30wt%.
[0010] Furthermore, in A3, the zinc loading is 2-2.2 wt %.
[0011] Furthermore, in A4, the specific operation of the dealumination treatment is as follows: the ratio of the zinc-loaded product to the 0.1 mol / L citric acid solution is 1 g: (16-20) mL, the mixture is placed in a constant temperature water bath at 85±5°C, and stirred at 180-220 rpm for 2-2.5 h.
[0012] Furthermore, in A4, the specific operation of calcination activation is as follows: pre-flow nitrogen (flow rate 45-50 mL / min) into the muffle furnace until the oxygen content is <0.1%, first raise the temperature to 300±5°C at 2-3°C / min, keep warm for 1 hour, then raise the temperature to 480±5°C at 1-1.5°C / min, keep warm for 3 hours, and cool with the furnace.
[0013] Furthermore, the secondary metal catalyst is a bimetallic catalyst.
[0014] Furthermore, the secondary metal catalyst is a Co-Cu catalyst.
[0015] This application has the following beneficial effects: In the preparation of the first-stage molecular sieve catalyst of the present invention, cerium nitrate, a cerium source, is introduced based on a molar ratio of phosphoric acid to a template agent of 1:(0.5-0.55). On the one hand, Ce acts as a "structural repair agent". The residual carbon formed by the high-temperature carbonization of excess di-n-butylamine is converted into a mesoporous pore-forming agent in the presence of cerium nitrate, etching mesopores on the micropore walls, increasing the proportion of mesoporous channels and improving the diffusion rate of synthesis gas. In addition, Ce 4+By oxygen vacancy migration, the skeleton distortion caused by excessive template is compensated, lattice defects are repaired, and the negative effects of excessive template are offset.
[0016] On the other hand, Ce acts as an "acid site regulator". The CeO2 nanoparticles formed by high temperature conversion preferentially anchor strong L acid sites, reduce side reactions, inhibit ethanol dehydration, and retain medium-strong B acid sites to promote CO insertion to generate CH3CO*. Moreover, CeO2 and Zn 2+ Formation of Ce-O-Zn heterojunction interface, Ce-O-Zn heterojunction interface optimizes electron transfer, Zn 2+ The d-band center of the product moves upward, enhancing the adsorption of *CH3CHO, reducing the H2 dissociation energy barrier, and increasing the acetaldehyde hydrogenation rate.
[0017] In summary, Ce, through its dual functional roles as a "structural repair agent" and an "acid site regulator," transforms excess templates from a "defect source" into a "mesopore generation aid," synergistically improving the diffusion efficiency and hydrogenation rate, thereby synergistically improving the ethanol yield. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a comparative trend chart of ethanol yields in Examples 1 to 3 and Comparative Examples 1 to 3 in the test examples of the present invention. DETAILED DESCRIPTION
[0019] The present application is further described in detail below with reference to the embodiments.
[0020] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.
[0021] Example 1: (I) Preparation of a primary molecular sieve catalyst, the preparation method is as follows: A1. Mix 100g of phosphoric acid solution (85% by weight) with 300g of deionized water, add the template agent di-n-butylamine, and add the molar ratio of phosphoric acid to di-n-butylamine to form a uniform gel. The mixture is stirred at 200r / min. Then, 175g of aluminum isopropoxide (aluminum source), 0.18g of cerium nitrate (cerium source), and 52g of silica sol (SiO2 content: 30wt%) are added to form a uniform gel.
[0022] A2. Transfer the gel obtained in A1 to a high-pressure reactor, microwave-heat to about 160°C, and crystallize for 6 hours; the product is centrifuged and washed until neutral, dried at 105°C for 12.5 hours, and calcined at about 550°C for 4 hours to remove the template to obtain a calcined product.
[0023] A3. The calcined product obtained in A2 was immersed in zinc nitrate solution, dried, and calcined at 450°C for 3.2h to obtain a zinc-loaded product; the zinc loading was 2.1wt%.
[0024] A4. Dealuminate the zinc-loaded product obtained in A3 with a citric acid solution. The specific procedure is: use a ratio of 1 g zinc-loaded product to 18 mL of 0.1 mol / L citric acid solution. Stir in a constant-temperature water bath at approximately 85°C and 200 rpm for 2.2 hours to form mesopores (improve diffusion efficiency). Calcinate and activate the product again. The specific procedure is: pre-flow nitrogen (50 mL / min) through a muffle furnace until the oxygen content is <0.1%. Raise the temperature to approximately 300°C at a rate of 2°C / min, hold at this temperature for 1 hour, then raise the temperature to approximately 480°C at a rate of 1°C / min, hold at this temperature for 3 hours, and cool in the furnace to obtain the primary molecular sieve catalyst.
[0025] (2) Preparation of Co-Cu catalyst, the preparation method is as follows: B1. Dissolve 10 g of Na2C2O4 in 350 mL of deionized water, add 4.4 g of copper nitrate trihydrate, and stir until a dark blue transparent solution is obtained. Seal the solution and let it stand at low temperature for 12 h. After crystallization is completed, filter it with suction, rinse with anhydrous ethanol, and dry it in an oven at 50°C for 6 h to obtain crystals. B2. Dissolve 3.02 g of cobalt nitrate hexahydrate, 12.69 g of zinc nitrate hexahydrate, and 8.00 g of aluminum nitrate nonahydrate in 200 ml of deionized water to obtain a mixed salt solution a. Dissolve 3.63 g of NaNO3 and 5.38 g of NaOH in 200 ml of deionized water to obtain a mixed salt solution b. Mixed salt solution a and mixed salt solution b are vigorously stirred in a three-necked flask to obtain a pink slurry-like precipitate. Continue to stir vigorously for 5 minutes, then heat to 100°C and slowly stir to crystallize for 12 hours. After filtering and washing with deionized water, wash with ethanol, and then dry in a vacuum oven at 60°C overnight, grind to obtain a powder. B3. Take the crystals obtained in B1 and the powder obtained in B2, mix them at a Co / Cu molar ratio of 1.5:1 to form a 0.015 mol / L mixed aqueous solution, add hydrotalcite powder in an amount of 0.5% of the mixed aqueous solution, stir at room temperature for 12 h, filter and wash, vacuum dry at 60°C for 12 h, and grind to obtain a Co-Cu catalyst.
[0026] (3) A method for producing sustainable aviation fuel using straw comprises the following steps: Synthesis gas and dimethyl ether are first introduced into a fixed-bed reactor. A catalytic reaction occurs over a primary molecular sieve catalyst at 220°C and 6 MPa to produce a primary product. The volume ratio of CO to H₂ in the synthesis gas is 1:1. The primary product is then passed over a Co-Cu catalyst for a catalytic reaction at 260°C and 12 MPa to produce a secondary product. The fixed-bed reactor containing the primary molecular sieve catalyst and the fixed-bed reactor containing the Co-Cu catalyst are connected in series. The secondary product is then separated to produce ethanol.
[0027] Example 2: The difference between this example and Example 1 is that a first-stage molecular sieve catalyst is prepared, and the preparation method is as follows: A1. Mix 100 g of phosphoric acid solution (85% by weight) with 290 g of deionized water, add the template agent di-n-butylamine, and add the molar ratio of phosphoric acid to di-n-butylamine to form a uniform gel. The mixture is stirred to form a uniform gel.
[0028] A2. Transfer the gel obtained in A1 to a high-pressure reactor, microwave-heat it to about 160°C, and crystallize it for 6 hours; the product is centrifuged and washed until neutral, dried at 105°C for 12 hours, and calcined at about 550°C for 4 hours to remove the template to obtain a calcined product.
[0029] A3. The calcined product obtained in A2 was immersed in zinc nitrate solution, dried, and calcined at about 450°C for 3.2 hours to obtain a zinc-loaded product; the zinc loading amount was 2 wt%.
[0030] A4. Dealuminate the zinc-loaded product obtained in A3 with a citric acid solution. The specific procedure is: use a 1g zinc-loaded product and 0.1mol / L citric acid solution ratio of 16mL. Incubate in a constant-temperature water bath at approximately 85°C, stirring at 180 rpm for 2.5 hours to form mesopores (improving diffusion efficiency). Activate the product by calcination again. The specific procedure is: pre-flow nitrogen (50mL / min) through a muffle furnace until the oxygen content is <0.1%. Raise the temperature to approximately 300°C at a rate of 2°C / min, hold at this temperature for 1 hour, then raise the temperature to approximately 480°C at a rate of 1°C / min, hold at this temperature for 3 hours, and cool in the furnace to obtain the primary molecular sieve catalyst.
[0031] Example 3: The difference between this example and Example 1 is that a first-stage molecular sieve catalyst is prepared, and the preparation method is as follows: A1. Mix 100 g of phosphoric acid solution (85% by weight) with 310 g of deionized water, add the template agent di-n-butylamine, and add the molar ratio of phosphoric acid to di-n-butylamine to form a uniform gel. The mixture is stirred to form a uniform gel.
[0032] A2. Transfer the gel obtained in A1 to a high-pressure reactor, microwave-heat it to about 160°C, and crystallize it for 6 hours; the product is centrifuged and washed until neutral, dried at 110°C for 12 hours, and calcined at about 550°C for 4 hours to remove the template to obtain a calcined product.
[0033] A3. The calcined product obtained in A2 was immersed in zinc nitrate solution, dried, and calcined at about 450°C for 3.2 hours to obtain a zinc-loaded product; the zinc loading amount was 2.2 wt%.
[0034] A4. Dealuminate the zinc-loaded product obtained in A3 with a citric acid solution. The specific procedure is: use a 1g zinc-loaded product and 0.1mol / L citric acid solution ratio of 1g:20mL. Stir in a constant-temperature water bath at approximately 85°C at 220 rpm for 2 hours to form mesopores (improving diffusion efficiency). Calcinate and activate again. The specific procedure is: pre-flow nitrogen (50mL / min) through a muffle furnace until the oxygen content is <0.1%. Raise the temperature to approximately 300°C at a rate of 2°C / min, hold at this temperature for 1 hour, then raise the temperature to approximately 480°C at a rate of 1°C / min, hold at this temperature for 3 hours, and cool in the furnace to obtain the primary molecular sieve catalyst.
[0035] Comparative Example 1: The difference between this comparative example and Example 1 is that the molar ratio of phosphoric acid to the template agent di-n-butylamine is 1:0.4, and cerium nitrate is deleted.
[0036] Specifically, a first-stage molecular sieve catalyst is prepared, and its preparation method is as follows: A1. Mix 100g of phosphoric acid solution (85% by weight) with 300g of deionized water, add the template agent di-n-butylamine, and add the molar ratio of phosphoric acid to di-n-butylamine to form a uniform gel. The mixture is stirred at 200r / min. Then, 175g of aluminum source aluminum isopropoxide and 52g of silica sol (SiO2 content is 30wt%) are added to form a uniform gel.
[0037] A2. Transfer the gel obtained in A1 to a high-pressure reactor, microwave-heat to about 160°C, and crystallize for 6 hours; the product is centrifuged and washed until neutral, dried at 105°C for 12.5 hours, and calcined at about 550°C for 4 hours to remove the template to obtain a calcined product.
[0038] A3. The calcined product obtained in A2 was immersed in zinc nitrate solution, dried, and calcined at 450°C for 3.2h to obtain a zinc-loaded product; the zinc loading was 2.1wt%.
[0039] A4. Dealuminate the zinc-loaded product obtained in A3 with a citric acid solution. The specific procedure is: use a ratio of 1 g zinc-loaded product to 18 mL of 0.1 mol / L citric acid solution. Stir in a constant-temperature water bath at approximately 85°C and 200 rpm for 2.2 hours to form mesopores (improve diffusion efficiency). Calcinate and activate the product again. The specific procedure is: pre-flow nitrogen (50 mL / min) through a muffle furnace until the oxygen content is <0.1%. Raise the temperature to approximately 300°C at a rate of 2°C / min, hold at this temperature for 1 hour, then raise the temperature to approximately 480°C at a rate of 1°C / min, hold at this temperature for 3 hours, and cool in the furnace to obtain the primary molecular sieve catalyst.
[0040] Comparative Example 2: This comparative example differs from Example 1 in that cerium nitrate is deleted.
[0041] Comparative Example 3: The difference between this comparative example and Example 1 is that the molar ratio of phosphoric acid to the template agent di-n-butylamine is 1:0.4.
[0042] Test Example: Test subjects: Examples 1-3 and Comparative Examples 1-3. Test item: Ethanol yield (based on primary molecular sieve catalyst). Test results: See Table 1.
[0043] Table 1. Test results of test cases Ethanol yield / g / kgcat / h Example 1 392.8 Example 2 387.7 Example 3 384.4 Comparative Example 1 358.7 Comparative Example 2 334.1 Comparative Example 3 372.5 Result analysis: Analyze Example 1-Example 3 and combine the data in Table 1 and Figure 1 It can be seen that in the process of producing ethanol from synthesis gas according to the present invention (Example 1 to Example 3), the ethanol yield is as high as 384.4 g / kgcat / h (calculated based on the primary molecular sieve catalyst) or more.
[0044] Analyze Example 1 and Comparative Examples 1-3 and combine the data in Table 1 and Figure 1 Specifically, a comparison between Comparative Examples 1 and 2 shows that, compared to the 1:0.4 molar ratio of phosphoric acid to template di-n-butylamine in the preparation of the primary molecular sieve catalyst in Comparative Example 1, the 1:0.52 molar ratio of phosphoric acid to template di-n-butylamine in the preparation of the primary molecular sieve catalyst in Comparative Example 2 resulted in a decrease in ethanol yield from 358.7 g / kgcat / h to 334.1 g / kgcat / h. This indicates that increasing the template di-n-butylamine dosage to an excessive level results in a decrease in ethanol yield.
[0045] This is mainly because the molar ratio of phosphoric acid to template agent decreased from 1:0.4 to 1:0.52. On the one hand, the template agent dibutylamine is excessive, and the residual amino carbide after high-temperature calcination blocks the micropores (pore diameter <1nm), hindering the diffusion of synthesis gas to the active center and reducing the contact efficiency of the reactants. On the other hand, the excessive template agent interferes with the orderly arrangement of the skeleton, causing local lattice distortion, resulting in uneven distribution of acid sites and reducing CO activation sites; it also causes Zn 2+ The loading site distortion weakens its hydrogenation ability for aldehyde intermediates, resulting in a decrease in ethanol selectivity.
[0046] Comparing Comparative Examples 1 and 3, we find that the addition of cerium nitrate in step A1 in Comparative Example 3 increases the ethanol yield from 358.7 g / kgcat / h to 372.5 g / kgcat / h compared to Comparative Example 1. This indicates that, based on a 1:0.4 molar ratio of phosphoric acid to the template agent di-n-butylamine in the preparation of the primary molecular sieve catalyst, the addition of cerium nitrate in step A1 can improve ethanol yield.
[0047] This is mainly because CeO2 is preferentially anchored at the strong Lewis acid (L acid) sites of the molecular sieve framework when cerium nitrate is added in step A1, forming a Ce-O-Al / Si coordination structure, which inhibits excessive dehydration and effectively blocks the dehydration pathway from ethanol to ethylene. The retained medium-strong Brønsted acid (B acid) sites promote the formation of key intermediates, enhance CO insertion ability, accelerate the formation of CH3CO* (acetyl) and improve the selectivity of C2 oxygenates. CeO2 and Zn 2+ Forming a Ce-O-Zn heterogeneous interface, the Ce-O-Zn structure changes the electron transfer path, making Zn 2+ presents an electron-deficient state (Znδ + ), enhances the adsorption energy of acetaldehyde (*CH3CHO), reduces the hydrogenation energy barrier, and increases the ethanol production rate.
[0048] By comparison with Example 1, it can be seen that the molar ratio of phosphoric acid to the template agent is reduced from 1:0.4 to 1:0.52; and the addition of cerium nitrate in step A1 can produce a synergistic effect and synergistically improve the ethanol yield.
[0049] This is mainly because Ce, through its dual functional roles as a "structural repair agent" and an "acid site regulator," converts excess templates from "defect sources" into "mesopore generation aids," synergistically improving the diffusion efficiency and hydrogenation rate, thereby synergistically improving the ethanol yield.
[0050] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any appropriate manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0051] In addition, the various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for producing sustainable aviation fuel using straw, comprising: first converting the straw into synthesis gas; then subjecting the synthesis gas to a catalytic reaction with dimethyl ether over a primary molecular sieve catalyst; and then subjecting the resulting catalytic product to a catalytic reaction over a secondary metal catalyst, followed by separation to produce ethanol; then converting the ethanol into ethylene; and finally converting the ethylene into aviation fuel; characterized in that: The preparation method of the primary molecular sieve catalyst is as follows: A1. Mix 100g of phosphoric acid solution with 290-310g of deionized water, add a template, and add 170-180g of aluminum source, 0.16-0.2g of cerium source, and 50-55g of silica sol under stirring to form a uniform gel. A2. Heat the gel obtained in A1 to 160±5°C and crystallize for 5.5-6.5 hours. Centrifuge and wash the product until neutral, dry it at 100-110°C for 12-13 hours, and calcine it at 550±10°C for 3.8-4.2 hours to obtain a calcined product. A3, immerse the calcined product obtained in A2 in a zinc nitrate solution, dry it, and calcine it at 450±10°C for 3-3.5h to obtain a zinc-loaded product; A4. The zinc-loaded product obtained in A3 is dealuminated with a citric acid solution and calcined again for activation to obtain a primary molecular sieve catalyst.
2. The method for producing sustainable aviation fuel using straw according to claim 1, characterized in that: In A1, the wt% of the phosphoric acid solution is ≥85%.
3. The method for producing sustainable aviation fuel using straw according to claim 1, characterized in that: In A1, the template is di-n-butylamine; the aluminum source is aluminum isopropoxide; and the cerium source is cerium nitrate.
4. The method for producing sustainable aviation fuel using straw according to claim 1, characterized in that: In A1, the SiO2 content in the silica sol is 30wt%.
5. The method for producing sustainable aviation fuel using straw according to claim 1, characterized in that: In A3, the zinc loading is 2-2.2 wt%.
6. The method for producing sustainable aviation fuel using straw according to claim 1, characterized in that: In A4, the specific operation of the dealumination treatment is as follows: the ratio of the zinc-loaded product to the 0.1 mol / L citric acid solution is 1 g: (16-20) mL, the mixture is heated in a constant temperature water bath at 85±5°C, and stirred at 180-220 rpm for 2-2.5 hours.
7. The method for producing sustainable aviation fuel using straw according to claim 1, characterized in that: In A4, the specific operation of calcination activation is as follows: pre-flow nitrogen into the muffle furnace until the oxygen content is <0.1%, first heat it to 300±5℃ at 2-3℃ / min, keep it at that temperature for 1h, then heat it to 480±5℃ at 1-1.5℃ / min, keep it at that temperature for 3h, and then cool it with the furnace.
8. The method for producing sustainable aviation fuel using straw according to claim 1, characterized in that: The secondary metal catalyst is a bimetallic catalyst.
9. The method for producing sustainable aviation fuel using straw according to claim 8, characterized in that: The secondary metal catalyst is a Co-Cu catalyst.
Citation Information
Patent Citations
Preparation method of bimetallic molecular sieve catalyst and application of bimetallic molecular sieve catalyst in olefin hydroformylation / hydrogenation
CN117563659A
Method for preparing sustainable aviation fuel based on biomass
CN118767973A
Catalyst for synthesizing methanol from synthesis gas and preparation method thereof
US20110118367A1
Catalysts and processes for the direct production of liquid fuels from carbon dioxide and hydrogen
US20210340075A1
Cited By
Green method for preparing sustainable aviation fuel through propylene oligomerization-hydrogenation
CN121759244A